International hospitality management (Harlow : Longman, 1996)
This book is divided into four parts: The International Environment; Competitive Strategies; Corporate Structures and Planning; and Corporate Systems and Analysis.
Keywords: Management; Hospitality industry; Hospitality industry -- Management